Computer Networking Principles, Protocols and Practice - Bonaventure, Olivier (Open textbook library., 2011)
This open textbook aims to fill the gap between the open-source implementations and the open-source network specifications by providing a detailed but pedagogical description of the key principles that guide the operation of the Internet.